Spatial ratio of two fungal genotypes content of Naematelia aurantialba and Stereum hirsutum in nutritional growth substrate and fruiting bodies reveals their potential parasitic life cycle characteristics - Jianqiong Lan; Yongkang Zhang; Yingli Cai; Xiaofei Shi; Kaixuan Zhang; Jiacheng Huang; Chengmo Yang; Xinhua He; Fuqiang Yu; Wei Liu (Journal of Agriculture and Food Research)
The JinEr (Golden Era) mushroom is a rare and nutritionally valuable macrofungus, prized for its unique bioactive compounds and culinary properties. It is believed to form heterogeneous fruiting bodies comprising two fungal species: Naematelia aurantialba and Stereum hirsutum. While, research on their interaction, particularly regarding the cellular composition ratio within the substrate and fruiting body was limited. In this study, through whole-genome comparisons of 56 species, we identified candidate genes with intra- and inter-specific variation. Nine species-specific fragments were selected, with four primer pairs validated after evaluating amplification efficiency and melting curves. By comparing Ct values from four species-specific primer pairs, we quantified the relative proportions of both genotypes and revealed their striking spatial partitioning. The outer apex of the fruiting body showed the closest proportions (S. hirsutum: N. aurantialba = 1.51:1), with S. hirsutum dominance increasing progressively downward to 3.97:1 (middle of fruiting body) and 6.52:1 (base of fruiting body). Across all fruiting body sections, S. hirsutum genotypes predominated (77.12 % of total content), demonstrating that most edible tissue derives from this species rather than the prized N. aurantialba. Below the fruiting body, genotype ratios exhibited exponential divergence: increasing to 16.28:1 at 3 cm below the base, and reaching 520.92:1 at the substrate midpoint, with N. aurantialba becoming undetectable in deeper substrate layers. These results establish that S. hirsutum serves as the primary metabolic engine for substrate decomposition and nutrient acquisition. Our findings support a refined life cycle model: S. hirsutum initially colonizes and degrades substrates, forming the structural foundation for subsequent parasitism by N. aurantialba during reproductive development, ultimately yielding deformed composite fruiting bodies. This study provides the first molecular-level characterization of fungal heterogeneity in JinEr mushrooms (Naematelia aurantialba/Stereum hirsutum complex), offering fundamental insights into their life cycle and practical guidance for cultivation optimization.